PENGARUH SIKAP DAN NORMA SUBYEKTIF TERHADAP NIAT BELI MASYARAKAT SEBAGAI KONSUMEN BIG TV PADA KELURAHAN SEI AGUL KECAMATAN MEDAN BARAT - Sitanggang, Darna (Jurnal Manajemen dan Bisnis, 2016)
The rise of information technology today, resulted in viewers want more information forms from abroad in the form of news and entertainment shows. The need for more extensive information, an opportunity for the satellite television station. Satellite TV is not to compete with each other is BIG TV, which is one of the satellite TV channel highest and the lowest in Indonesia, both SD (standard definition) and HD (high definition), while becoming a satellite TV pay-first serving HD channels more lots for its customers. From the description, the problem in this research is formulated as follows: "Is the consumer attitudes and subjective norms significantly influence consumer intentions to buy BIG TV on agul Sei Village West district of Medan." This study aimed to analyze the influence of consumer attitudes, subjective norms influence on consumer intentions to buy BIG TV and to know how consumer intentions to buy BIG TV on agul Sei Village West district of Medan. The benefits of research is to give an overview of consumer attitudes and subjective norms on consumer intentions to buy BIG TV on agul Sei Village West district of Medan. The study population was Sei agul community in the Village West district of Medan. Samples were taken 96 people. The required data were collected using a questionnaire. Data analysis technique used is descriptive method by using the theory of planned behavior. From the discussion concluded that the average value of the consumer attitude variables (Ab) of 2.42. That is, the public / consumer in the village of Sei agul be positive (very strong) against BIG TV. The average value of the variable subjective norm (SN) of 0.32. That is, the public / consumer in the village of Sei agul convinced and got positive motivation (strong enough) of the group preferred to subscribe BIG TV. Behavioral intention equation: BI = 0,8229Ab + 0,1770SN. Behavior public / consumer in the village of Sei agul to subscribe BIG TV is more influenced by consumer attitudes that is equal to 0.8229 (82.29%) compared to the subjective norm, amounting to 0.1770 (17.70%). Advice given to the management of BIG TV is that companies provide more training earnestly to marketers, giving higher incentives so that they are more spirit in introducing and providing services to customers and to the community BIG TV.